PENGENALAN RUMAH ADAT NUSANTARA MELALUI PELATIHAN MELUKIS PADA GENERASI MUDA - Fivanda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
In the last 3 (three) years the development of technology and digitalization has been very rapid, especially in Indonesia. For children at elementary school level, the development of creativity really needs to be improved and sharpened. Including cultural preservation activities and maintaining knowledge about local wisdom. Children aged between 6 and 12 years always show unique characteristics and are highly curious about things in their surroundings. These abilities need to be sharpened and awareness increased in the socio-cultural field. In this way, the PKM team continues to collaborate and collaborate with the Rumah Pagi Bahagia Foundation partners in Bintaro. Collaborative activities continued through training activities on painting hats. The aim of this activity is to introduce, grow and preserve Indonesian cultural arts for children aged 6-12 years through painting traditional Indonesian houses. The activity method uses training methods through instructors and video modules. The activity started from the preparation stage, the PKM team carried out observations of partners, distribution of painting supplies and equipment. Followed by the implementation stage of the PKM team as instructors supported by video tutorials that have been prepared by the PKM team. In the exploration stage, the image of the shape of an Indonesian traditional house begins with providing references as an introduction, then continues with developing the shape and decorations painted on the caping hat. The result of this PKM activity is a caping hat that has been painted with various decorations from Indonesian traditional houses such as Toraja, Balinese, Papuan traditional houses and so on. It is hoped that the variations in the results of painting on hats will have a positive impact and produce products that have artistic value. It is hoped that this training can continue to be carried out by introducing the culture of the Indonesian archipelago. This PKM activity provides an opportunity for children to increase their creativity while learning about culture.